Pengaruh Perbandingan Tepung Millet Kecambah Fermentasi dan Maizena Terhadap Karakteristik Brownies - Kharismawati, Ni Putu; Kartika Pratiwi, I Desak Putu; Diah Puspawati, Gusti Ayu Kadek (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2022)
The research aimed to determine the effect comparison of fermented sprouts millet flour with corn starch to the characteristics of brownies and to find out the best comparison of fermented sprouts millet flour with corn strach to produce brownies with the best characteristics. This study used a completely randomized design with a comparison of fermented sprouts millet flour with corn starch treatment, consisting of 6 levels namely: 100%:0%, 95%:5%, 90%:10%, 85%:15%, 80%:20%, 75%:25%. The treatment was repeated 3 times to obtain 18 experimental units. The data was analyzed with analysis of variance and if the treatment had a significant effect, then followed by the Duncan Multiple Range Test. The results showed that the comparison of millet flour and cornstarch in brownies had a significant effect (P<0.05) on the moisture content, ash content, protein content, crude fiber content, tannin content, color, aroma, taste, overall acceptance of brownies. The comparison of fermented sprouts millet flour and cornstarch 80%:20% was the best characteristics of brownies with a water content 15.13%, ash content 1.59%, protein 8.78%, crude fiber 12.74%, and tannin 4.91%, color and texture slightly liked, odor, taste, and overall acceptance liked, brown color, soft and not crumbly.